3.1k views
2 votes
C) 4x-9y = 17 6x - 5y = 17​

1 Answer

4 votes

Answer:

(2, - 1 )

Explanation:

4x - 9y = 17 → (1)

6x - 5y = 17 → (2)

multiplying (1) by 6 and (2) by - 4 and adding will eliminate x

24x - 54y = 102 → (3)

- 24x + 20y = - 68 → (4)

add (3) and (4) term by term to eliminate x

0 - 34y = 34

- 34y = 34 ( divide both sides by - 34 )

y = - 1

substitute y = - 1 into either of the 2 equations and solve for x

substituting into (1)

4x - 9(- 1) = 17

4x + 9 = 17 ( subtract 9 from both sides )

4x = 8 ( divide both sides by 4 )

x = 2

solution is (2, - 1 )

User Lundman
by
5.5k points